2016
DOI: 10.1016/j.rboe.2016.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Q-angle in patellofemoral pain: relationship with dynamic knee valgus, hip abductor torque, pain and function

Abstract: ObjectiveTo investigate the relationship between the q-angle and anterior knee pain severity, functional capacity, dynamic knee valgus and hip abductor torque in women with patellofemoral pain syndrome (PFPS).MethodsThis study included 22 women with PFPS. The q-angle was assessed using goniometry: the participants were positioned in dorsal decubitus with the knee and hip extended, and the hip and foot in neutral rotation. Anterior knee pain severity was assessed using a visual analog scale, and functional capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 27 publications
(42 reference statements)
3
35
0
6
Order By: Relevance
“…These lateral musculatures include the quadratus lumborum, external oblique, internal oblique, iliocostalis, longissimus, and intertransversalis. 22 These muscles serve as the key dynamic stabilizers of the spine and lumbopelvic region especially during a reaction-based task such as running. This task is a common skill needed in football.…”
Section: Discussionmentioning
confidence: 99%
“…These lateral musculatures include the quadratus lumborum, external oblique, internal oblique, iliocostalis, longissimus, and intertransversalis. 22 These muscles serve as the key dynamic stabilizers of the spine and lumbopelvic region especially during a reaction-based task such as running. This task is a common skill needed in football.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the transverse correction of the hip resulted in a decreased dynamic knee valgus pattern. The dynamic knee valgus is characterised by an excessive hip adduction and internal rotation angle and an increased pronation of the foot [8,11] and creates a lateral force vector on the patella that is associated to increased patellofemoral joint stress [38]. The patellofemoral joint stress reaches a peak during the early and mid stance phase [39] and thus most injuries, such as patellofemoral pain occur as a result of the high impact forces at the time of the initial contact during running [40].…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ] Fukuda et al [ 12 ] demonstrated that a 4-week hip abductor and external rotator muscle exercises were effective in pain, function, and functional strength improvement in patients with PFPS. Almeida et al [ 13 ] explored the association of dynamic knee valgus with hip abductor strength, pain, and function in PFPS. They observed that dynamic knee valgus (Q angle of knee) had no correlations with hip abductor muscle strength, pain, or function in women with PFPS.…”
Section: Introductionmentioning
confidence: 99%